2003
DOI: 10.1094/cchem.2003.80.6.654
|View full text |Cite
|
Sign up to set email alerts
|

Staling of Bread: Role of Amylose and Amylopectin and Influence of Starch‐Degrading Enzymes

Abstract: Cereal Chem. 80(6):654-661The present investigation aims at understanding the mechanism of bread firming during staling. Changes in the starch fraction due to the addition of amylases and their influence on the texture of bread crumb were studied during aging and after rebaking of stale bread. Pan bread was prepared by a conventional baking procedure. The influence of three different starch-degrading enzymes, a conventional a-amylase, a maltogenic a-amylase, and a b-amylase were investigated. The mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
148
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 25 publications
10
148
2
Order By: Relevance
“…Bread staling is a significant factor that leads to decreases in bread texture quality. 8) Little information is available as to how the physical properties of bread containing gelatinized rice starch change over time. Our objective in this study was to investigate the effects of rice porridge on the texture and viscoelastic properties of bread and to compare them with those of wheat flour and rice flour bread during storage.…”
mentioning
confidence: 99%
“…Bread staling is a significant factor that leads to decreases in bread texture quality. 8) Little information is available as to how the physical properties of bread containing gelatinized rice starch change over time. Our objective in this study was to investigate the effects of rice porridge on the texture and viscoelastic properties of bread and to compare them with those of wheat flour and rice flour bread during storage.…”
mentioning
confidence: 99%
“…This indicates that the water absorption of the dough with BG was higher. This effect was due to the water retention ability of this polymer resulting from the hydrophilic nature of most gums (GUARDA et al, 2004;CHRISTIANSON et al, 1981;COLLAR;ARMERO;MARTÍNEZ, 1999;GURKIN, 2002;TWILLMAN;WHITE, 1988). Perhaps, this behavior can demonstrate that during cooking, the hydrocolloid forms a network that could act as a barrier to the diffusion of gases, which in turn would reduce vapor losses resulting in higher moisture content of crumb bread Crumb moisture content Moisture content was determined in fresh and stored samples, according to the AACC official method (method 925.10) (AMERICAN..., 1995).…”
Section: Effect Of Bg Addition On the Quality Of Fresh Crumbsmentioning
confidence: 99%
“…The starch in the crumbs supplemented with BG, is provided with a certain amount of water that is less than that of the control crumb, but enough to act as a plasticizer in the reorganization of the amylopectin molecule. Rogers et al (1988) concluded that starch retrogradation and hardening of the crumb are uncorrelated with each other in a certain range of moisture contents and, according to several authors, the moisture content close to 40% would highly favor starch retrogardation and bread firming (DAVIDOU et al, 1996;HE;HOSENEY, 1990;ROGERS et al, 1988;). …”
Section: Effect Of Bg On the Crumb Staling During Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Some other authors obtained seemingly contradicting results when either decreases (Yasunaga et al 1968) or increases (Xu 1985) were found out in viscosity with storage times. Bakery improvers such as enzymes (amylases, lipases, proteases, pentosanases), emulsifiers, hydrocolloids, and their blends serve as additives to improve technological (rheological) and texture properties of dough and slow down the staling of bread and bakery products (Hug-Iten et al 2003;Bárcenas & Rosell 2005;Jiang et al 2005;Moayedallaie et al 2010;Rosell & Santos 2010;Patel et al 2012, etc.). The addition of improvers (mostly in ppm amount) affects the standard quality of dough and bread and also the staling process of bread.…”
mentioning
confidence: 99%